Effect of bilateral uterine artery ligation in cases of postpartum hemorrhage on ovarian reserve - Abo Zaid, Mohamed A.; Hagras, Ahmed M.; Hefeda, Mohamed M.; Hwidy, Medhat S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Bilateral uterine artery ligation (BUAL) is a fertility-preserving procedure used in women experiencing postpartum hemorrhage (PPH). However, the long-term effects of this procedure on ovarian reserve remain unclear. Aim to investigate the effect of BUAL in cases of PPH on ovarian reserve, Methods: This study was carried out at department of obstetrics and gynecology Tanta university on 40 patients divided into 2 groups: (The study group); included 20 patients underwent cesarean section with successful BUAL for intractable atonic PPH, (The control group); included 20 patients underwent cesarean section without BUAL; during a period between April 2020 and December 2021, Results: There is no-significant difference between study and control group according to AMH (ng/ml), resistivity index (RI) and pulsatility index (PI) of right and left uterine artery and ovarian artery after 6 months of bilateral UAL, Conclusions: Bilateral UAL had no negative effects on ovarian reserve or ovarian blood supply, so this treatment should be used as a fertility preservation technique to avoid hysterectomy in patients experiencing PPH.